Inflammation Drives Alzheimer's Disease: Emphasis on 5-lipoxygenase Pathways - Siddiqui, Aisha; Akhtar, Sayeed; Shah, Zahoor; Othman, Iekhsan; Kumari, Yatinesh (Current Neuropharmacology, 2021)
It is a known fact that inflammation affects several physiological processes, including the functioning of the central nervous system. Additionally, impairment of lipid mechanisms/pathways have been associated with a number of neurodegenerative disorders and Alzheimer’s Disease (AD) is one of them. However, much attention has been given to the link between tau and beta- amyloid hypothesis in AD pathogenesis/prognosis. Increasing evidences suggest that biologically active lipid molecules could influence the pathophysiology of AD via a different mechanism of inflammation. This review intends to highlight the role of inflammatory responses in the context of AD with the emphasis on biochemical pathways of lipid metabolism enzyme, 5-lipoxygenase (5- LO).
Keywords: Lipid Molecule